Hepatoprotective effects of methanolic extract of Alcea rosea against acetaminophen-induced hepatotoxicity in mice - Liaqat Hussain; Muhammad Sajid Hamid Akash; Madeha Tahir; Kanwal Rehman; Khwaja Zafar Ahmed (Bangladesh Pharmacological Society, 2014)
The aim of this study was to evaluate the hepatoprotective effects of Alcea rosea against acetaminophen-induced hepatotoxicity in mice. Aqueous methanolic extract of A. rosea were given orally for 7 consecutive days followed by daily toxic dose of acetaminophen. At the end of treatment period, evaluation of hepatoprotective activity of A. rosea was done on basis of levels of liver enzyme markers (aminotransferases, alkaline phosphatase and bilirubin) and histopathological examination of liver tissues. Acetaminophen significantly increased serum levels of liver enzyme markers whereas, the extract of A. rosea significantly reduced serum levels of elevated liver enzyme markers in dose-dependent manner compared to acetaminophen treated mice group. Histopathological examination of liver tissues also supported the protective effects of A. rosea on liver enzyme markers. We conclude that extract of A. rosea has strong hepatoprotective effects against acetaminophen-induced hepatotoxicity; thereby, affirming its traditional therapeutic role in liver injury.